Linguistic Imperialism: Native-Speakerism from The Perspective of Non-Native English Learners - Silalahi, Ronald Maraden Parlindungan (Journal of ELT Research, 2019)
Native-Speakerism is an ideology that focuses on the belief that the best model and teacher in foreign language learning (specifically English) are native speakers of that language. In the context of English Language Teaching (ELT); the native speaker of English are considered more capable of representing western culture appropriately in accordance with their social and cultural contexts (Holliday 2005: 6). This ideology explicitly shows the phenomenon of linguistic imperialism and inequality in ELT. In Teaching English as a Foreign Language (TEAFL); the phenomenon of Native-Speakerism is still debatable. A number of Indonesian-English teachers and learners realize the importance of learning English in the western context, but others do not rule out the possibility of learning English in a non-western context. Referring to this dualism, this article discusses the way in which Indonesian non-native English learners view the ideology of Native-Speakerism. This study uses a qualitative method to collect the data. Focus Group Discussion with 60 Non-Native English Learners were conducted to find out the learners' perceptions of Native-Speakerism. The informants are the native Indonesian students from a number of the English departments (such as, English Literature, English Language and Culture, or English education) from several private universities in Jakarta. This article shows that the native-speakerism ideology developed in the context of TEAFL. Non-native English Speaking Teachers and Native English Speaking Lecturers have equal opportunities in TEAFL because teaching is not only measured by the teacher's linguistic and contextual abilities but also the ability to manage the class accurately and precisely. This research is expected to be beneficial for the development of English language learning in Indonesia. In addition, the results of this study are expected to encourage the development of appropriate English learning methods in Indonesia.